CONSUMER PREFERENCES FOR INDONESIAN FOOD - Hani Ernawati; Dodik Prakoso (Journal of Indonesian Economy and Business (JIEB), 2020)
Introduction/Main Objectives: Food industries have been growing fast in Indonesia for recent decade, so it is necessary for food companies to understand Indonesian consumer attitudes and examine how Indonesian consumption behavior may change in consuming food. Background Problems: The development of society, with the concept of modernization at this time, encourages the interest people have for consuming food from other countries, so that Indonesian food is increasingly being displaced in its own country. Novelty: The results of this study provide a method for evaluating the combination of different attributes for food combinations, which can be used as a reference for selling food. Research Methods: This research used a conjoint analysis to explore consumers’ preferences for different cuisines, especially Indonesian cuisine. Findings/Results: Compared with previous studies, the origin of food is an important food attribute, whilst “western food” is the preferred type of food. Conclusion: Western food being the most preferred type of food, followed by Indonesian food, a crispy and salty taste, fresh food is preferred, as is food at a cheap price. Price was the most important attribute.